Barriers, facilitators and pathways of a lung cancer screening (LCS) programme: COBELT co-design. (20th October 2021) - Brown, L; Sullivan, F; Treweek, S; Haddow, A; Mountain, R; Selby, C; Beusekom, M van
Abstract:  : Lung cancer (LC) is one of the most common causes of cancer death globally. Adults aged 55+, (ex)-smokers and living in areas of deprivation are at greater risk from lung cancer. Leading to a 20% decrease in mortality rates, screening with Low Dose CT (LDCT) is a promising means of detecting LC early. Autoantibody biomarker blood tests may play a role in identifying people suitable for LDCT screening, forming a national LCS programme. To increase the likelihood of the success of such a programme, suitable ways of providing the service must firstly be identified. A 2-phase co-design process, with 2 population groups. Group 1-Aged 55+, (ex)-smoker, high deprivation (N = 39). Group 2-Health and community professionals (N = 16). Phase 1: Interviews and focus groups. Conversations focussed on barriers, facilitators and potential pathways for the uptake and provision of a biomarker blood test and LCS. Phase 2: Interactive surveys (offline/online), focussing on the prioritisation of key barriers and solution generation. Qualitative data was transcribed and analysed using thematic analysis. Descriptive statistics were generated for quantitative data. Phase 1 identified key barriers, facilitators and pathways for uptake and provision. Service users indicated options for uptake and a means to embed the programme in the community as essential. From the perspective of providers, capacity and time for provision were key. Phase 2 found a home test kit was the preferred method of blood test for service users (independently or with assistance). Service providers leaned towards provision via venesection. Barriers were ranked by service users, the most dominant barrier was Fear of test result. Working in a collaborative manner has led to the identification of new knowledge and insights regarding the best means to target a future LCS programme to those who may benefit most. Future implementation of such a programme should consider the results from this study. This is a CSO funded project. Key messages: This process has illuminated key barriers, facilitators and pathway options that could improve the implementation of a LCS programme, using an autoantibody blood test to identify LDCT candidates. Measures to overcome barriers from both the perspective of the service users and providers are necessary to ensure the success of the LCS programme.